Konservasi Temuan Makam Kuno Keramat dan Perkembangan Islam di Medan - Sumanti, Solihah Titin (FIKRAH, 2021)
the purpose of this research is to find out how the distribution of the existence of ancient tombs in the city of Medan, the form of management of ancient tombs in the city of Medan based on the Law of Cultural Heritage No. 11 of 2010, and the contribution of the findings of ancient tombs to the development of Islam in the Village Martubung Medan. The method used is transect walk. This method is carried out as a strategy to map the existence of cultural heritage from the existence of complexes of ancient tombs.  His findings that the identification of ancient tombs in the city of Medan, especially in Martubung village, namely the Tomb of Datuk Hasan, Tomb of Datuk Payung, Tomb of Datuk Tongah, Datuk Dadih and Tomb of Datuk Hitam. To maintain the cultural heritage, the government collaborates with local communities to conduct socialization and conservation activities that include physical protection, transfer, excavation and recording, maintenance. The discovery of five ancient Islamic tomb complexes in Martubung Village shows the historical events of the entry and development of Islam in North Sumatra and cultural changes through the process of human adaptation to the environment.